Tuber Skin Colour Variation In The Segregating Populations Of Potatoes (Solanum Tuberosum L.) (Applied Biological Research, 2023)
The skin colour of potato tubers is one of the most noticeable visual  characteristics and ranges from white-cream to black in appearance. A study  was conducted to understand tuber skin colour variation in potatoes using  contrasting parents. A set of 327 segregating progenies of 8 populations, developed by using ‘CP 4242’ as female (2 crosses) and male (6 crosses) were  assessed for tuber skin colour. Based on the presence or absence of colour, the  segregating progenies were classified into 5 skin colours viz., white-cream, light  red, dark red, light purple and dark purple with the help of potato colour chart.  The 327 segregating progenies of 8 crosses exhibited a prevalence of 137 (41.9%),  71 (21.7%), 12 (3.7%), 17 (5.2) and 90 (27.5%) in dark purple, light purple, dark  red, light red and white-cream tuber skin colours, respectively. In totality  72.48% progenies possessed coloured tuber skin (dark purple, purple, dark red  and light red) as compared to 27.52% progenies exhibiting white-cream skin  colour, reflecting 3:1 segregation ratio of tuber colour variation in potato  breeding population. This reveals the dominance of purple colour over white in  the segregating population.
Keywords: Potatoes; segregating population; tuber colour variation